Penggunaan Partikel Sae, Shika, dan Dake dalam Novel Botchan Karya Natsume Soseki - Adi Suardika, I Made (Humanis; Vol 22 No 4 (2018), 2018)
This research entitled “Use of particles sae, shika and dake in Botchan ’s Novel by Natsume Soseki”. The theories used for analyzing are syntax theory by Nitta (1997), theory of fungtions by Sunagawa (1991), and contextual meaning theory by Chaer (2007). Based on the analysis that has been done, there are two forms of sae, three forms of shika, and four forms of dake . For the funtions and meanings of sae are reinforces a part, indicates terms, and shows unconditionally. The funtions and meanings of shika show the smallest amount, the limits of action, and emphasize one thing only. Th e funtions and meanings of dake shows limitations, levels, habits, and affirmation of another.